2019
DOI: 10.3390/fluids4010026
|View full text |Cite
|
Sign up to set email alerts
|

Stenosis Indicators Applied to Patient-Specific Renal Arteries without and with Stenosis

Abstract: Pulsatile flow in the abdominal aorta and the renal arteries of three patients was studied numerically. Two of the patients had renal artery stenosis. The aim of the study was to assess the use of four types of indicators for determining the risk of new stenosis after revascularization of the affected arteries. The four indicators considered include the time averaged wall shear stress (TAWSS), the oscillatory shear index (OSI), the relative reference time (RRT) and a power law model based in platelet activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Additionally, in general, it can be observed that regions downstream of stenosis had lower TAWSS and higher OSI, which constitute risk factors for the incidence and progression of atherosclerosis [33]. These results are in good agreement with recent studies conducted in arterial stenosis [31], [33], [47].…”
Section: %supporting
confidence: 89%
See 3 more Smart Citations
“…Additionally, in general, it can be observed that regions downstream of stenosis had lower TAWSS and higher OSI, which constitute risk factors for the incidence and progression of atherosclerosis [33]. These results are in good agreement with recent studies conducted in arterial stenosis [31], [33], [47].…”
Section: %supporting
confidence: 89%
“…It has also been observed that oscillatory WSS promotes atherosclerosis [31], [33]. However, this information is not given by the TAWSS.…”
Section: G Post-processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Wall Shear Stress-Sensitivity of Results to Boundary Condition. To assess the effect of change in inlet geometry and sensitivity to BCs, the following commonly used WSS related parameters were used: TAWSS, the OSI, and the relative residence time (RRT) [38,39].…”
Section: Resultsmentioning
confidence: 99%